(untitled) (Ozone Therapy Global Journal, 2015)
Background: Lumbar discopathy is a major cause of pain and disability in the economically active population; deteriorating the quality of life of the patients. Case presentation: The patient is a 26 year old from Salvador, who attend to an specialist in pain medicine with a history of eleven months of suffering back pain. At the time of the consultation he has the antecedent two hospitalizations and multiple consultations with neurosurgeon and physiatrist. The patient was treated with ozone at a concentration of 20 μg/mL using 10 mL for infiltration. 12 sessions of paravertebral ozone (the first 5 sessions on consecutive days, then on alternate days) and 12 epidural sessions (one every 5 days) were administered. Evolution was monitored by means of VAS scale and according to the clinic symptoms. The results were the gradual and total recovery of motor and sensory damage L5 root. At the sixth session the patient was free of symptoms (pain and paresthesia). With the onset of the physical rehabilitation, the motor function was recovered without sequelae in the march